Resource competition as a mechanism for B cell homeostasis - McLean, A. R. (The National Academy of Sciences of the USA, 1997)
Cellular competition for survival signals offers a cogent and appealing mechanism for the maintenance of cellular homeostasis [Raff, M. C. (1992) Nature (London) 356, 397–400]. We present a theoretical and experimental investigation of the role of competition for resources in the regulation of peripheral B cell numbers. We use formal ecological competition theory, mathematical models of interspecific competition, and competitive repopulation experiments to show that B cells must compete to persist in the periphery and that antigen forms a part of the resources over which B cells compete.